2003
DOI: 10.1111/j.1476-5829.2003.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear scanning with99mTc‐HDP for the initial evaluation of osseous metastasis in canine osteosarcoma

Abstract: The purpose of this retrospective analysis was to evaluate the use of nuclear scintigraphy in determining the rate of secondary sites of osseous malignancy at initial presentation in dogs with osteosarcoma. Radiographs of suspicious secondary lesions were reviewed and placed into four separate categories: benign lesions; no lesion seen on radiographs; subtle radiographic changes suggestive of, but not conclusive for, metastasis; and metastatic lesions highly suspected on radiographs. Three hundred and ninety-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
4
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 9 publications
1
24
4
1
Order By: Relevance
“…Canine osteosarcoma can metastasise to other bony sites and a large study was performed to assess the utility of staging using scintigraphy. While the interpretation of nuclear scans can be subjective, this study revealed only a 7.8 per cent chance of detecting unsuspected osseous metastasis in canine osteosarcoma patients (Jankowski and others 2003). Given the cost and low availability of the required equipment in the UK, scintigraphy is unlikely to form part of routine staging for canine and feline tumours.…”
Section: Stagingmentioning
confidence: 66%
“…Canine osteosarcoma can metastasise to other bony sites and a large study was performed to assess the utility of staging using scintigraphy. While the interpretation of nuclear scans can be subjective, this study revealed only a 7.8 per cent chance of detecting unsuspected osseous metastasis in canine osteosarcoma patients (Jankowski and others 2003). Given the cost and low availability of the required equipment in the UK, scintigraphy is unlikely to form part of routine staging for canine and feline tumours.…”
Section: Stagingmentioning
confidence: 66%
“…A recent study showed that 8% of dogs with appendicular osteosarcoma present with asymptomatic metastatic or synchronous lesions to other bones. 4 The prognosis CORRESPONDENCE for dogs with secondary lesions is poor with median survival times of approximately 2 months compared to 12 months for dogs with no evidence of metastatic disease at the time of diagnosis. 2 Furthermore, limb amputation for treatment of the primary tumour may result in catastrophic failure through a second bone lesion because of the combination of weakened bone due to the neoplastic process and redistribution of body weight as a result of the amputation.…”
Section: Jm Liptak Department Of Clinical Studiesmentioning
confidence: 99%
“…In dogs with primary appendicular OS, additional bone lesions at diagnosis have been considered metastatic in nature and described to range in prevalence from 1.4 to 28% . However, synchronous appendicular bone tumors in dogs occur without evidence of other metastatic foci within the skeleton or lungs .…”
mentioning
confidence: 99%
“…5,7 In dogs with primary appendicular OS, additional bone lesions at diagnosis have been considered metastatic in nature and described to range in prevalence from 1.4 to 28%. [8][9][10][11] However, synchronous appendicular bone tumors in dogs occur without evidence of other metastatic foci within the skeleton or lungs. 12 Scarce information is available regarding prevalence of secondary bone lesions at diagnosis in dogs with primary extracranial axial OS.…”
mentioning
confidence: 99%